Attitudes and Behaviors of Self-Medication Among Hajj Pilgrims in Batu City - Wijaya, Dhani; Rahmadanita, Fathia Faza; Syarifuddin, Sadli; Rochman, Mochammad Cholilur; Kho’im, Khoiron Nur (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 4 (2024): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v4i0.3308, 2025)
Self-medication is the practice of selecting and using medications on one's own without a doctor's prescription. Every individual must have qualified knowledge, attitudes, and behaviors to do self-medication. Self-medication is very important for a person in maintaining his health, including when performing Hajj. Self-medication measures can help Hajj pilgrims to achieve istithaah conditions and maintain their health in Saudi Arabia. The purpose of this study was to determine the attitude and self-medication behavior of Hajj pilgrims in Batu City. This study included descriptive observational using cross sectional survey method. The sampling this study using of consecutive sampling approach. Data collection was carried out through filling out questionnaires that have been tested for validity and reliability. The results of the study on 60 hajj pilgrims in Batu City showed that 75.83% of pilgrims were self-medicated in the "good" categories of attitude and 76.4% of Hajj pilgrims were also in the "good" categories of behavior. Based on this, it can be concluded that the attitude and self-medication behavior of the Batu City Hajj pilgrims were good.